Finite Element Method Analysis of Potential Shaft Breakage in Truck Wheel Drive Due to Initial Crack - Fauzan; Sarah Niaci; Rahmad Afandi; Zaim Hikma Nasution (Fakultas Teknik Universitas Samudra, 2023)
The need for truck transportation in the city of Langsa is increasing. This is because the residents of Langsa use trucks as a means of transporting palm oil from plantations. Engine component failures are often experienced in every mechanical construction, and these failures are marked by the breaking of these engine components. Cracks become one of the potential sources of failure in the machine structure. There is a need to detect cracks in the shaft at an early stage to prevent damage. Therefore, it should be investigated using appropriate techniques at the early stage of crack formation. The purpose of this research is to find the potential source of shaft fracture relative to the initial crack location on the shaft. This research method is carried out by determining the same initial crack dimensions at two different locations. The initial crack locations are determined through a case study of frequent fractures in the fillet spline and fillet flange locations. The calculation results show that the permissible stress of the shaft is 80.7 MPa. The finite element method simulation results show that the maximum shear stress value on the shaft without an initial crack is 65.234 MPa, on the shaft with an initial crack in the fillet spline location is 69.654 MPa, and on the shaft with an initial crack in the fillet flange location is 78.79 MPa. The finite element method simulation results also show that the von Mises shear stress value on the shaft without an initial crack is 113.29 MPa, on the shaft with an initial crack in the fillet spline location is 120.66 MPa, and on the shaft with an initial crack in the fillet flange location is 137.23 MPa. The finite element method simulation results further show that the von Mises shear strain value on the shaft without an initial crack is 0.000567, on the shaft with an initial crack in the fillet spline location is 0.000630, and on the shaft with an initial crack in the fillet flange location is 0.000693. In conclusion, the potential source of failure experienced by the shaft between the two locations of frequent failure is the shaft with an initial crack in the fillet flange location.